In Defence of Democratic Dirty Hands. Issue 160 (1st September 2019) - Nick, Christina
Abstract : This paper considers three arguments by David Shugarman and Maureen Ramsay for why dirty hands cannot be democratic. The first argues that it is contradictory, in principle, to use undemocratic means to pursue democratic ends. There is a conceptual connection between means and ends such that getting one's hands dirty is incompatible with acting in accordance with democratic ends. The second claims that using dirty-handed means, in practice, will undermine democracy more than it promotes it and therefore cannot be justified. The final criticism states that politicians with dirty hands are a sign that politics is no longer meeting the criteria necessary to be called democratic. The paper shows that such rejections of democratic dirty hands are based on misunderstandings of the nature of dirty hands and democratic politics.